Spatiotemporal Phytochrome Signaling during Photomorphogenesis: From Physiology to Molecular Mechanisms and Back - Montgomery, Beronda L. (Frontiers in Plant Science, 2016)
Light exposure results in distinct responses in specific seedling tissues during photomorphogenesis. Light promotes growth of cotyledons and leaves, as well as development and elongation of roots, whereas light inhibits elongation of hypocotyls. For distinct plant responses such as shade avoidance, far-red light or shifts in spectral light quality similarly have disparate impacts on distinct plant tissues, resulting in elongation of stems or petioles and a reduction in growth of leaf blades for many species. The physiological bases of such tissue- and organ-specific light responses were initially studied using localized irradiation of specific tissues and organs, or irradiation of dissected plant parts. These historical approaches were used to identify spatial-specific pools of photoreceptors responsible for regulating local, i.e., tissue- or organ-specific, or distal, i.e., interorgan, plant responses. The red/far-red responsive phytochromes have been the most widely studied among photoreceptors in this regard. Whereas, the spatial localization of photoreceptors regulating many tissue- or organ-specific light responses were identified, the underlying signaling networks responsible for mediating the observed responses have not been well defined. Recent approaches used to investigate the molecular bases of spatiotemporal light responses include selective irradiation of plants harboring mutations in specific photoreceptors, tissue-specific expression of photoreceptors, primarily in photoreceptor mutant backgrounds, or tissue-specific biochemical ablation of photoreceptor accumulation. Progressive integration of such approaches for regulating the availability of localized pools of phytochromes with the use of transcriptomic or proteomic analyses for assessing the genes or proteins which these spatially discrete pools of phytochrome regulate is yielding emergent insight into the molecular bases of spatiotemporal phytochrome signaling pathways responsible for regulating spatiotemporal light responses of which we have been aware of at the physiological level for decades. Here, I discuss historical and emerging approaches to elucidating spatiotemporal signaling mediated by phytochromes during photomorphogenesis.